the PENGEMBANGAN PERANGKAT PEMBELAJARAN STEM BERBANTUAN VIDEO PEMBELAJARAN UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK POKOK BAHASAN FLUIDA DINAMIS - Muhammad Dwikhi Mursyam Aldi; Aris Doyan; Susilawati Susilawati (Postgraduate, University of Mataram, 2022)
This development research aims to test the feasibility of STEM learning tools assisted by learning videos to improve students' understanding of the concept of dynamic fluid dynamics. This research is included in Research and Development (R&D) with a 4D model consisting of Define, Design, Develop, and Disseminate. The products developed are syllabus, Learning Implementation Plan, Student Worksheets, concept understanding test instruments, and learning videos. The technique of collecting feasibility data uses a validation questionnaire that is assessed by six validators, namely three lecturers and three practicing teachers. The results of data analysis using a Likert scale show that the overall average of the device reaches 3.45 with the category of 86.65% (valid). From the results of these data, it can be concluded that the product developed is suitable for use in the learning process.